(NnOTNAQ TETRAD_ aNNY mAGDALENY bAH(B.(NdLQ FORTEPIANOs (NNOTY(B.s - (Ni(B.(Ns(B.(NbAHs; (Nl(B.(Ni(B.(NrOJZMANs (NREDAKTORs ((NsANKT(B-(NpETERBURGs (NlAN_s (NpLANETA mUZYKIs, 2021)
(NdWE nOTNYE TETRADI aNNY mAGDALENY bAHA(B.s
(N|TA nOTA(B.s
Keywords: (NFORTEPIANOs